TOLERANCE AND RELIGIOUS SOCIAL INTERACTION AT THE GONDOMANAN TEMPLE IN YOGYAKARTA - Shihabuddin, Aris; Mukhlis Ardianto, Muhammad (Pusat Studi Kebudayaan Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2024)
This paper is the result of field research that tries to see the dynamics of social interaction and religious tolerance in the Fuk Ling Miau Temple in Gondomaman, Yogyakarta. This research is interesting because in one temple there are three religions, namely Confucianism, Taoism, and Buddhism. On the other hand, the architecture of the temple is an acculturation of Chinese and Javanese culture. This research will use a qualitative method. This method was chosen because it emphasizes the depth of value. This method will try to answer how the choice of action to be interpreted and given a certain meaning. The results of this study found that the Gondomanan temple has unique characteristics due to the acculturation of Chinese and Javanese culture. The three religious’ adherents between confucianism, Taoism, and Buddhism look good in social interaction and tolerance as evidenced by interactions not only with the three religions, but also, they interact with other religious adherents, namely Christians and Muslims. Furthermore, the existence of these three places of worship as a tangible manifestation of religious plurality illustrates the willingness to accept and respect differences in beliefs during a multicultural society.